Praktik Kewargaan dalam Arena Institusi Informal Era Demokratisasi - Kamil, Insan (Indonesian Journal of Political Studies, 2021)
Most studies on citizenship have only focus on the practice of citizenship in the context of formal state institutions. On the other hand, there are relatively few studies discussing citizenship practices in informal institutions. Therefore, this study examines the practice of citizenship in Islamic boarding schools/pesantren in the form of bonds as jamaah. This article intends to map the operation of pesantren as a binder of social ties between its citizens, as well as the pattern of relations between kiai and santri. This research shows that pesantren acts as lebenschraum habitus which installs the perceptions and expressions of its citizens. Pesantren is also a locus of power that has a significant influence on political and civic practices. As a locus of power, there is symbolic capital which is represented and reproduced continuously so that the symbolic capital produces economic, social, and cultural capital. The surplus of capital owned by the lora enables them to transform from the habitus of pesantren, to the habitus of political society and the state through the mechanism of electoral democracy. Even though the pesantren with all their supporting elements have a clientelistic relationship pattern, there is a public morality that can be transformed to strengthen the democratization agenda in the future.